Peran Bimbingan dan Konseling Islam dalam Mengurangi Beban Psikologis pada Sandwich Generation di Era Modern - Eryanti Nurmala Dewi; Meiviana Nurul Khadijah Maulana; Dewi Sa’diah; Nani Nuranisah Djamal (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The phenomenon of the sandwich generation is increasingly evident in the modern era, in which productive-age individuals are required to meet the needs of both their parents and their children, resulting in financial and psychological pressure. This study examines the role of Islamic Guidance and Counseling (IGC) in reducing psychological burdens through spiritual, emotional, and social approaches. Using a descriptive qualitative method based on literature review, the findings reveal that IGC plays a significant role in enhancing inner peace, religious coping, and balance of family roles by reinforcing Islamic values such as patience (sabr), trust in God (tawakkul), gratitude (shukr), and contentment (qana’ah). Furthermore, Islamic counseling support helps individuals build emotional resilience and discover meaning in life amid the dual responsibility pressures. Therefore, IGC serves as an effective strategy to prevent and mitigate psychological impacts on the sandwich generation in the modern era.